Religious Values and Public Attitudes Toward the Sound Horeg Tradition: Evidence from a Quantitative Correlational Study - Zahrotun Ni’mah Afif; Taufiqurrahman Hasyim Salengke; Mihmidaty Ya’coub; Chumaidah (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The Sound Horeg tradition has become a prominent form of popular culture in East Java, Indonesia, generating diverse public responses because of its perceived social, environmental, and moral implications. While some communities regard it as a cultural expression and source of entertainment, others question its compatibility with religious values and social norms. This study examined the relationship between understanding religious values and public attitudes toward the Sound Horeg tradition. A quantitative correlational survey design was employed involving 30 purposively selected respondents from communities familiar with the phenomenon. Data were collected through a structured questionnaire and analyzed using Pearson product–moment correlation after instrument validity, reliability, normality, and linearity assumptions had been confirmed. The findings revealed a statistically significant and very strong positive relationship between understanding religious values and public attitudes toward the Sound Horeg tradition (p < 0.001; r = 0.971). Individuals with a stronger understanding of religious values tended to demonstrate more critical and responsible evaluations of cultural practices that may influence social harmony and moral standards. These findings contribute to the literature on the interaction between religiosity and public attitudes toward contemporary cultural practices and provide practical insights for community leaders and policymakers seeking to balance cultural preservation with religious and social considerations